Evaluasi Kapasitas Kolam Retensi PT. Tactical Garment Garut Menggunakan Storm Water Management Model 5.2 - Sulwan Permana; Ayu Nur Isti Ajijah (Jurnal Konstruksi, 2026)
Flooding is a serious problem that often occurs due to uncontrolled land use change. This study aims to evaluate the capacity of the retention pond at PT Tactical Garment Garut in controlling runoff using the Storm Water Management Model (SWMM) version 5.2. PT Tactical Garment Garut, located in Haruman Village, Leles Subdistrict, Garut Regency, faces challenges in managing runoff due to the conversion of vegetated land into covered land for the construction of an apparel industry. The research method involved hydrological and hydraulic modeling using SWMM to calculate the 5-year and 10-year return period channel discharge, and determine the effectiveness of the existing retention ponds. The modeling results showed that the retention pond was able to accommodate a maximum runoff of 89.55 m³/sec for 6 hours. The maximum inflow (total water discharge) into the retention pond is 961.29 m³. However, the calculation of the effectiveness of the retention pond shows that the retention pond is only able to cope with 1.04% of the incoming flood volume, which indicates that the capacity of the retention pond is inadequate. This study suggests further evaluation of the capacity of the retention pond as well as possible expansion or infrastructure improvements to enhance the flood handling capability of the area.